Corn crop performance in an Ultisol compacted by tractor traffic - Moraes, Moacir Tuzzin de; Levien, Renato; Trein, Carlos Ricardo; Bonetti, João de Andrade; Debiasi, Henrique (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to determine whether compaction by tractor traffic in areas managed under controlled traffic can be limiting to corn crop, under different tillage systems, in a Typic Paleudult of medium texture. Two experiments were carried out, one in the field over two crop seasons and another in a greenhouse. The treatments consisted of minimum tillage with chiselling; no-tillage subjected to one, three, or six passes of a tractor weighing 3.8 Mg; and an area without traffic. Evaluations were performed for soil physico-hydraulic parameters (soil bulk density, penetration resistance, and water retention curve), root and shoot growth, and grain yield. The agricultural traffic increased bulk density, soil penetration resistance, and water content at field capacity. The highest values for soil penetration resistance (1,600 kPa) and bulk density (1.67 g cm-3) in the trafficked soil were not limiting to corn development and increased grain yield for both crop seasons. Tractor traffic of up to six passes is beneficial to corn cultivation, and it increases water availability and corn grain yield.